Framework do prototypowania gier komputerowych - Rams, Przemysław (My University, 2015)
Praca opisuje główne elementy oraz proces powstawania frameworku. Przedstawia wykorzystane w tym celu technologie open source. Powstała aplikacja stanowi zestaw narzędzi oraz szablon dla tworzenia prototypów gier komputerowych. Praca udowadnia, że możliwe jest osiągnięcie celu wykorzystując wiedzę i technologie dostępne w internecie.

Thesis describes creation and main parts of the framework. It shows open source technologies used to achieve this goal. The result is an application that may be used as a toolset and template for game prototypes. Thesis proves that it is possible to achieve a goal by using knowledge and technology available in the internet.
Game prototyping framework
Keywords: framework; open source; programowanie; gry komputerowe; programming; games